Globalizing the Board and Financial Performance : Evidence from Nigerian Banks - Olubukunola, Uwuigbe; Uwalomwa, Uwuigbe; Iyoha Francis, O.; Ehimare, Omankhanlen Alex (Indian Journal of Finance, 2016)
The board of directors is crucial and very important in a business control structure. The value of boards in decision making and increasing the wealth of shareholders depends on how well directors perform their functions. However, the role of foreign independent directors (FIDs) in a firm can never be over emphasized. It is expected that they can improve the advisory role of boards because of direct information about international markets. This study, therefore, investigated if there is a significant difference between the performance of firms with and those without FIDs. The paper observed that a non- significant relationship existed between the tested parameters. This non-substantial difference is likely to be due to the fact that international directors have a tendency to adjust to the socio-organizational values of the location in which they function from. The study, therefore, recommends that FIDs should be encouraged because of their different backgrounds. This will enable them to add to the firm’s values and various skills which some domestic board members do not possess. In order to encourage both minority and majority foreign investors, foreign board members should be allowed on boards for assurance that the corporation is being managed by professionals in their best interests.